THE INFLUENCE OF SELF-CONFIDENCE AND GRIT ON ANXIETY IN THE WORLD OF WORK - Dimas Adi Wijaya; Lolita Laily; Komang Maha Dewi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Problems arise when students who are looking for jobs consider the job search process difficult and related to negative emotions (Wanberg, 2010). Negative emotions can take many forms, one of which is anxiety. Anxiety disorders refer to emotional states marked by physical symptoms, unpleasant feelings of tension, and generally occurring bad things (Nevid, 2005). Anxiety in facing the world of work can reduce work performance or even become worse. Anxiety can cause fear of public speaking, fear of interacting with important figures in a company, fear of taking on new challenges, and fear that makes a person appear restless and anxious (Jones, 2020). Greenberger and Padesky (2016) state that there are four aspects of anxiety in facing the challenges of the world of work, namely thoughts, behavior, physical reactions, and mood. Anxiety can emerge because individuals are not confident in their competencies; this becomes one factor causing fear and worry among final-semester students regarding the possibility of obtaining a job, which creates a lack of self-confidence (Sari & Astuti, 2014). Students should have high self-confidence in responding to all matters, including anxiety in facing the world of work. Perry (2005) reveals that self-confidence enables a person to overcome new challenges, believe in oneself in difficult situations, pass limiting barriers, complete things they have never done before, and fully express their talents and abilities. In addition to self-confidence, Nevid, Rathus, and Greene (2005) state that one factor causing anxiety in facing the challenges of the world of work is lack of social support. Individuals with insufficient social support will feel that they are not cared for, not appreciated, and do not have someone who can help them find work. Therefore, this study tests the hypothesis that there is a relationship between self-confidence and social support with anxiety in facing the world of work. This study aims to examine the relationship among variables, namely students' self-confidence and grit with anxiety in facing the world of work. This research is expected to provide an overview of students' conditions before entering the world of work. The research method used is quantitative research with final-year students as subjects. Subject selection in this study uses purposive sampling, namely a sampling technique with certain considerations based on predetermined criteria in the study (Sugiyono, 2016). The targeted output of this research is the writing of an article submitted to a journal so that its benefits can be felt by the community.